Filtering toolbox development - Qing, Xiangyue (2013)
With the development of digital signal processing technology, it is now possible to process audio signals with various acoustic effects. For instance, by applying a low pass filter with a certain cutoff frequency to a piece of music, noise can be removed from it, returning a signal with much better quality. And by analyzing the digital samples of a female’s voice speech, we can reconstruct it to make it sound like a male’s voice speech. These effects are not only very interesting but also widely useful in a number of industries.